2014
DOI: 10.1103/physrevb.90.014102
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and transformation kinetics of small helium clusters in bulk tungsten

Abstract: The production of energy through nuclear fusion poses serious challenges related to the stability and performance of materials in extreme conditions. In particular, the constant bombardment of the walls of the reactor with high doses of He ions is known to lead to deleterous changes in their microstructures. These changes follow from the aggregation of He into bubbles that can grow and blister, potentially leading to the contamination of the plasma, or to the degradation of their mechanical properties. We comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 60 publications
9
77
1
Order By: Relevance
“…The Finnis-Sinclair type potential proposed by Ackland and Thetford [21], which has been widely used in the literature [10,12,13,[15][16][17], was adopted for the interactions between W atoms. For the interactions between the He and W atoms, we used a pairwise potential that was constructed by fitting its long range part to ab initio data and smoothly connecting the long range part to Ziegler-Biersack-Littmark (ZBL) potential in the short range part [19].…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Finnis-Sinclair type potential proposed by Ackland and Thetford [21], which has been widely used in the literature [10,12,13,[15][16][17], was adopted for the interactions between W atoms. For the interactions between the He and W atoms, we used a pairwise potential that was constructed by fitting its long range part to ab initio data and smoothly connecting the long range part to Ziegler-Biersack-Littmark (ZBL) potential in the short range part [19].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…There is also chance for a helium atom to dissociate from a trapping site and to return to diffusion status [15]. For the diffusion behaviours of the He atoms and the small He clusters in the bulk W, MD studies were conducted by Wang et al [19], Zhou et al [15] and Perez et al [16]. These studies found the non-Arrhenius diffusion of He atoms at high substrate temperatures and some counter-intuition features for the migration of small He clusters (e. g., He 5 cluster migrates faster than He 4 cluster).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as interstitial He cluster grow, they reach a point where they are able to eject W atoms from the lattice and condense into the resulting vacancies, creating the nuclei of a bubble that can then grow and disrupt the structure of the material (see Refs. [36,37] for further details and results on that system). The reference temperature is set to T 0 = 3500 K (upper temperature boundary of right plot in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although small clusters can migrate [201,202], the assumption is justified because cluster diffusion slows down with the cluster size and is strongly suppressed by impurities and interstices [67,195,203]. In addition, trap mutation reactions would trap the pure He n clusters [157,204]. Trap mutation consists of the growth of He n (in the case of pure He atoms in interstitial positions is also named self-trapping [157]) and He n V m clusters by trapping He.…”
Section: Simulation Methodsmentioning
confidence: 99%